Skin wounds in premature newborns hospitalized in a neonatal intensive care unit - Fontenele, Fernanda Cavalcante; Cardoso, Maria Vera Lúcia Moreira Leitão (Rev Rene, 2005)
We aimed at identifying and describing the characteristics of skin wounds that affected the preterm newborns (PTN) hospitalized in a Neonatal Intensive Care Unit (NICU). It is an exploratory, descriptive and quantitative study. The sample was composed of all PTNs hospitalized in the NICU of a public maternity ward who presented lesions during the period of data collection and whose parents authorized their participation in this research. We employed the direct observation of the newborns during the assistance, in order to detect any wound that would appear. The corporal area where there were more lesions were the face and the scalp, the majority of them being abrasive lesions with hyperemia and with lost of small areas of the epidermis, and lesions of dark color without solution of continuity, measuring, mostly, less than one centimeter. We found out that the number of skin lesions in preterm newborns is still significantly high, in spite of all the care given to their skin.